Interprofessional Communication from the Perspective of Physiotherapy and Midwifery Lecturer - Savirani, Rifda; Widyandana, Doni; Claramita, Mora (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Effective Interprofessional communication, is one of the essential aspect for optimizing collaboration among healthcare professionals, which in turn enhances patient outcomes and service quality. The World Health Organization advocates for early implementation of Interprofessional Education (IPE) at the university level to prepare students as competent collaborators in healthcare settings.Aims: This study aims to explore physiotherapy and midwifery lecturer’s perceptions regarding learning methods, enabling factors, and inhibiting factors in interprofessional communication as preliminary step before conducting IPE training for lecturers. Methods: This exploratory qualitative study employed focus group discussions with 5 physiotherapy and 6 midwifery lecturers. Data were analyzed using deductive content analysis guided by the 2016 IPEC (Interprofessional Education Collaborative) framework.Results: All participants had experience in interprofessional communication, and realized that as health workers, collaboration is inseparable, with one important aspect is communication. Ten enabling factors were identified, the use of media and communication methods, language, good listeners, feedback, respect differences, communicate the importance of teamwork, sufficient knowledge, leaders and policies, commitment and self-awarness and continuing communication. And eight inhibiting factors were obtained including the use of communication media, language and cultural differences in perception and no feedback, lack of understanding regarding the importance of teamwork, lack of interaction, internal factors and differences in education level.Conclusion: The study revealed both enabling and inhibiting factors in interprofessional communication, along with recommendations for learning methods. These findings provide a basis for developing and evaluating effective IPE training for lecturers.